The Right to Say No: Customary Land Rights, Extractive Industries and the Need for Free, Prior and Informed Consent - Mc Lean, Richard Stowe (Department of Public Law, 2022)
Compared to the more “traditional” Civil or socio-economic rights, which are regarded as being held by individuals; the notion that communities can also be holders of particular rights is still relatively new. And yet, the suffering inflicted on customary communities by states, corporations and even individuals dates back to the colonial modes of production, wherein colonial authorities would extract raw materials from colonies. This being the case, it is important for any modern system for the protection of human rights – especially on the African continent - to take the unique circumstances of communities adversely affected by extractive industries into account. It is with this in mind, that my dissertation aims to offer an in depth analysis of the legal relationship between the interests of extractive projects and the rights of communities affected by such projects. As I am writing from a South African context, a significant percentage of my research is concerned with how this relationship plays out in South Africa – with particular attention being paid to the cases of: the Xolobeni Community1 in the rural Eastern Cape, the Bakgatla Ba Kgafela in the North West2 and the Somkhele Community in Kwa-Zulu Natal3 . However, I do also address the broader context by spending an entire chapter dealing with the international, regional and sub-regional mechanisms which can have an impact on the rights of mining affected communities. I also spend a significant part of my research arguing in favour of the standard of Free, Prior and Informed Consent as the minimum standard of community involvement in the decision making process relating to project that might affect them (colloquially known as “FPIC”). These arguments are based on the findings of a number of theorists and legal practitioners who have found that the lack of FPIC is one of the most significant stumbling blocks for the promotion and protection of the rights of mining affected and other marginalised communities. It is my hope that this research will serve as the basis for discussions around these issues in academia and practice with the end goal of advancing the rights of communities affected by mining or other extractive operation.